(untitled) (The Research of Medical Science Review, 2024)
In Pakistan, forensic cases that are referred for psychological assessment have increased multifold in past few years. The needs of forensic clientele sometimes differ significantly from those of the conventional clinical clientele. Lack of familiarity with the specific needs may deeply impact the quality of clinical services provided to this sensitive clientele. Literature however, revealed a significant gap about the forensic psychiatric cohort in Pakistan, therefore, the present study was aimed to study the social, personal and psychiatric characteristics specific of this cohort. Forensic cases referred for psychological assessment in specialized psychiatric facilities of Lahore were reviewed thoroughly. In total, 462 cases were selected for in depth review based on the inclusion criteria. The average age of the individuals was observed to be 29±11.34 years and men were noted to be in majority. Most individuals were single and had varying educational background. Results provided information related to personal characteristics, psychological disorders, reason for assessment referral etc. The findings were discussed in context of broader empirical context. Forensic psychiatric cases differ from conventional clinical clientele in several ways and understanding the idiosyncratic needs of this cohort requires to first identify the social and clinical characteristic of profiles of this cohort which ll be helpful in identifying their needs.